Long-term clinical outcomes of endoscopic submucosal dissection for colorectal neoplasms in 423 cases: a retrospective study - Yamada, Masayoshi; Saito, Yutaka; Takamaru, Hiroyuki; Sasaki, Hayato; Yokota, Takuya; Matsuyama, Yasushi; Sato, Yoshinori; Sakamoto, Taku; Nakajima, Takeshi; Taniguchi, Hirokazu; Sekine, Shigeki; Matsuda, Takahisa (Endoscopy, 2017)
Background and study aim Endoscopic submucosal dissection (ESD) is known as a curative treatment for colorectal superficial neoplasms. There is however a need for more long-term clinical data to establish the full advantages of colorectal ESD regarding very low recurrence rates. The aim of this retrospective study was to determine long-term clinical outcomes of colorectal ESD.Methods A total of 423 lesions treated by ESD for colorectal adenoma/dysplasia or adenocarcinoma between 1998 and 2008 at a single high volume referral center were included. We conducted a retrospective survey on patients with follow-up and obtained complete 1-, 3-, and 5-year outcome data for 358 (85 %), 292 (69 %), and 209 (49 %) lesions, respectively. Curative resection was defined when the pathological specimen had carcinoma-free resection margins, irrespective of piecemeal or en bloc resection, without submucosal deep invasion (≥ 1000 µm), lymphovascular involvement, or a poorly differentiated adenocarcinoma component.Results After a median 4.9 years of follow-up, the 3-year overall cumulative endoscopic recurrence rate and cancerous recurrence rate were 2.9 % (95 % confidence interval [95 %CI] 1.2 – 4.7) and 1.1 % (0 – 2.1), respectively. The 5-year overall cumulative endoscopic recurrence and cancerous recurrence rates were 3.8 % (1.7 – 5.9) and 1.6 % (0.1 – 3.0), respectively. In 361 lesions eligible for endoscopic follow-up, the 3-year endoscopic recurrence and cancerous recurrence rates were 2.4 % (0.8 – 4.1) and 0.4 % (0 – 1.4), respectively. Multivariate analysis revealed that piecemeal resection and submucosal deep tumor invasion were associated with recurrence.Conclusions The current study demonstrated favorable long-term clinical outcomes of colorectal ESD when en bloc curative resection is achieved.